2021
DOI: 10.46234/ccdcw2021.244
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Multidrug-Resistant Bacterial Infections in Non-Adult Patients — Zhejiang Province, China, 2014–2019

Abstract: Introduction Antimicrobial resistance has become a major public health threat globally. The prevalence of multidrug-resistant (MDR) bacterial infections increased substantially among inpatients under 18 years of age in recent years. In Zhejiang Province, China, the trends of drug-resistance in non-adult patients from 2014 to 2019 were monitored, aiming to determine the variation patterns and epidemiological features of MDR strains. Methods Patient data were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“… 1 , 11 , 12 Notably, ESBL-producing Enterobacterales were classified as one of the most significant pathogens in the World Health Organization’s list of priority pathogens. 13 , 14 A nationwide survey conducted in China revealed that the prevalence of ESBL-producing Enterobacterales was as high as 40.6%. 14 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 1 , 11 , 12 Notably, ESBL-producing Enterobacterales were classified as one of the most significant pathogens in the World Health Organization’s list of priority pathogens. 13 , 14 A nationwide survey conducted in China revealed that the prevalence of ESBL-producing Enterobacterales was as high as 40.6%. 14 …”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 A nationwide survey conducted in China revealed that the prevalence of ESBL-producing Enterobacterales was as high as 40.6%. 14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The timely and effective application of antibiotics is crucial for managing the morbidity and mortality of the infection ( Ferrer et al, 2014 ; Falcone et al, 2020 ). According to the report of the Chinese National Bacterial Drug Resistance Monitoring Network, Pseudomonas aeruginosa isolated from blood samples during 2014–2019 had the highest composition proportion, the second was A.baumannii ( Wu et al, 2021 ). In our previous studies, K.pneumonia was the most commonly isolated Gram-negative bacteria in affected intensive care unit (ICU) patients, the second was E. coli , and A.baumannii was in the third place ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%